Diabetic Cardiomyopathy: An Immunometabolic Perspective - Mishra, Paras K.; Ying, Wei; Nandi, Shyam Sundar; Bandyopadhyay, Gautam K.; Patel, Kaushik K.; Mahata, Sushil K. (Frontiers in Endocrinology, 2017)
ABSTRACT The heart possesses a remarkable inherent capability to adapt itself to a wide array of genetic and extrinsic factors to maintain contractile function. Failure to sustain its compensatory responses results in cardiac dysfunction, leading to cardiomyopathy. Diabetic cardiomyopathy (DCM) is characterized by left ventricular hypertrophy and reduced diastolic function, with or without concurrent systolic dysfunction in the absence of hypertension and coronary artery disease. Changes in substrate metabolism, oxidative stress, endoplasmic reticulum stress, formation of extracellular matrix (ECM) proteins and advanced glycation end products (AGEs) constitute the early stage in DCM. These early events are followed by steatosis (accumulation of lipid droplets) in cardiomyocytes, which is followed by apoptosis, changes in immune responses with a consequent increase in fibrosis, remodeling of cardiomyocytes, and the resultant decrease in cardiac function. The heart is an omnivore, metabolically flexible, and consumes the highest amount of ATP in the body. Altered myocardial substrate and energy metabolism initiate the development of DCM. Diabetic hearts shift away from the utilization of glucose, rely almost completely on fatty acids as the energy source, and become metabolically inflexible. Oxidation of fatty acids is metabolically inefficient as it consumes more energy. In addition to metabolic inflexibility and energy inefficiency, the diabetic heart suffers from impaired calcium handling with consequent alteration of relaxation-contraction dynamics leading to diastolic and systolic dysfunction. Sarcoplasmic reticulum (SR) plays a key role in excitation-contraction coupling as Ca2+ is transported into the SR by the SERCA2a (sarcoplasmic/endoplasmic reticulum ATPase 2a) during cardiac relaxation. Diabetic cardiomyocytes display decreased SERCA2a activity and leaky Ca2+ release channel resulting in reduced SR calcium load. The diabetic heart also suffers from marked downregulation of novel cardioprotective microRNAs discovered recently. Since immune responses and substrate energy metabolism are critically altered in diabetes, the present review will focus on immunometabolism and microRNAs.